2015
DOI: 10.3329/bmrcb.v40i2.25182
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gingivitis, Plaque accumulation and Decayed, Missing and Filled Teeth among slum population in Bangladesh

Abstract: A cross-sectional survey, using cluster sampling technique, of slum population, was done to explore the oral health status and the prevalence of common oral diseases. A close ended questionnaire comprising Decayed, Missing and Filled Teeth (DMFT) Index, Gingival Index (Löe and Silness) and Plaque Index was applied to evaluate and record oral diseases, in both male and female population, covering a wide range of age groups. Clinical examination was carried out in different slum set ups, including slum schools b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…The Silness and Löe plaque index (1964) was used to record the dental plaque in the sample studied. [18][19][20] The plaque index's score is determined based on the amount of dental plaque at the gingival margin, which is assessed by passing a WHO probe across the gingival margin.…”
Section: Methodsmentioning
confidence: 99%
“…The Silness and Löe plaque index (1964) was used to record the dental plaque in the sample studied. [18][19][20] The plaque index's score is determined based on the amount of dental plaque at the gingival margin, which is assessed by passing a WHO probe across the gingival margin.…”
Section: Methodsmentioning
confidence: 99%
“…A multi‐center study with South American adult population showed that the prevalence of gingival inflammation was 96.5% . The literature is consistent in reporting prevalence ratio of gingivitis higher than 90% in different populations . It is well known that untreated gingivitis may progress to destruction of periodontal tissues in susceptible individuals .…”
Section: Introductionmentioning
confidence: 97%
“…14 The literature is consistent in reporting prevalence ratio of gingivitis higher than 90% in different populations. 15,16 It is well known that untreated gingivitis may progress to destruction of periodontal tissues in susceptible individuals. 17 However, the mechanisms involved in this process or the reason why some sites present continuous gingival inflammation, but do not progress to tissue destruction are not established.…”
mentioning
confidence: 99%
“…Prevalence of gingivitis and plaque accumulation among study population was also significantly high. 7 Similar study conducted by Davidson et al to see the dental health issues among newly arrived refugees in Australian community. They used DMFT index (decayed, missing and filled teeth) as a measure of dental health status and compared data with the available records of public dental services.…”
Section: Discussionmentioning
confidence: 80%